Individual variation in field metabolic rates of wild living fish have phenotypic and ontogenetic underpinnings: insights from stable isotope compositions of otoliths - Jones, Joseph; Hunter, Ewan; Hambach, Bastian; Wilding, Megan; Trueman, Clive N. (Frontiers in Ecology and Evolution, 2023)
Individual metabolism has been identified as a key variable for predicting responses of individuals and populations to climate change, particularly for aquatic ectotherms such as fishes. Predictions of organism standard metabolic rate (SMR), and the thermal sensitivity of metabolic rate are typically based on allometric scaling rules and respirometry-based measures of respiratory potential under laboratory conditions. The relevance of laboratory-based measurement and theoretical allometric rules to predict performance of free-ranging animals in complex natural settings has been questioned, but determining time averaged metabolic rate in wild aquatic animals is challenging. Here we draw on stable isotope compositions of aragonite in fish otoliths to estimate time averaged experienced temperature and expressed field metabolic rate (FMR) simultaneously and retrospectively at an individual level. We apply the otolith FMR proxy to a population of European plaice (Pleuronectes platessa) from the North Sea during a period of rapid warming between the 1980s to the mid-2000s, sampling otolith tissue grown in both juvenile and adult stages. Among-individual variations in realised mass-specific FMR were large and independent of temperature and scaled positively with body size in adult (year 4) life stages, contradicting simplistic assumptions that FMR follows scaling relationships inferred for standard metabolic rates (SMR). In the same individuals, FMR in the first summer of life co-varied positively with temperature. We find strong evidence for the presence of consistent metabolic phenotypes within the sampled population, as FMR in the first year of life was the strongest single predictor for among individual variation in FMR at the point of sampling. Nonetheless, best fitting models explained only 20% of the observed variation, pointing to large among-individual variation in FMR that is unexplained by body mass, temperature or metabolic phenotype. Stable isotope-derived estimates of field metabolic rate have great potential to expand our understanding of ecophysiology in general and especially mechanisms underpinning the relationships between animal performance and changing environmental and ecological conditions.